Farmers Learning Exchange - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The learning exchange was organized by CCAFS, IIED and Andes. Farmers from the coastal regions of Kenya, The Eastern Himalaya in India and the Quechua comunities of the Peruvian Andes met during four days to visit the Potato Park and learn from each others experiences concerning climate change and adaptation practices. Photocredit: Manon Koningstein (CIAT)